Gratitude Journaling and Emotional Well-Being in Brazil - Lima, Adriana (Journal of Advanced Psychology, 2025)
Purpose: The purpose of this article was to analyze gratitude journaling and emotional well-being in Brazil. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Studies in Brazil show that gratitude journaling enhances emotional well-being by increasing happiness, life satisfaction, and positive emotions while reducing depression and anxiety. Daily gratitude lists yield similar benefits to event reporting, improving mental health. Unique Contribution to Theory, Practice and Policy: The broaden-and-build theory, cognitive appraisal theory may be used to anchor future studies on the gratitude journaling and emotional well-being in Brazil. Mental health practitioners and educators should consider integrating structured gratitude journaling into therapeutic interventions and wellness programs. Stakeholders should advocate for the inclusion of evidence-based gratitude practices in national mental health strategies, emphasizing low-cost, scalable interventions that complement traditional therapies.